Analysis of Effects of Sun's Position in the Sky on Solar Radiation and Solar Panel Output Power - Jazayeri, Moein; Uysal, Sener; Jazayeri, Kian (IEEE, 2013)
It is basically approved that the output power of a solar cell/module directly depends on the amount of solar irradiance which it receives from the sun. Also it is known that the irradiance values are not constant at any specific time interval. The changes in the position of the sun with respect to earth are one of the main reasons causing the variations in the amount of incoming sunlight and its energy to the earth's surface. The main focus of this paper is to analyze the effects of changes in the position of the sun in the sky on the incoming solar radiation during a whole year. Also the effects of such changes on the hourly values of solar radiation as well as the effects on the output power generated by a solar panel during a specific sample day is analyzed.
AFRICON Conference -- SEP 09-12, 2013 -- IEEE Reg 8, Pointe aux Piments, MAURITIUS
Keywords: solar energy; solar power generation; solar radiation; irradiance; photovoltaic cells; data acquisition; data analysis